Rehabilitation of shoulder impingement syndrome and rotator cuff injuries: an evidence-based review. Issue 5 (6th April 2010) - Ellenbecker, Todd S; Cools, Ann
Abstract : Rehabilitation of the patient with glenohumeral impingement requires a complete understanding of the structures involved and the underlying mechanism creating the impingement response. A detailed clinical examination and comprehensive treatment programme including specific interventions to address pain, scapular dysfunction and rotator cuff weakness are recommended. The inclusion of objective testing to quantify range of motion and both muscular strength and balance in addition to the manual orthopaedic clinical tests allows clinicians to design evidencebased rehabilitation programmes as well as measure progression and patient improvement.